Evaluating entomological measures and cypermethrin use in pest control - Susanto, Agus; Kesuma, Agung Puja; Zufri, Armen; Putra, Rizki Maisar; Wahono, Tri; Astuti, Endang Puji (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to analyze entomological indicators and the susceptibility status of the Aedes aegypti mosquito to cypermethrin in the Tanjung Balai Karimun Port Health Office area. Methods: This type of study is observational, using a cross-sectional design approach. Entomology indicator data collection is carried out routinely every month by observing containers in each building both inside and outside. The vulnerability test uses the WHO susceptibility test method. Results: The results of entomological indicators in the perimeter area showed no density of Aedes aegypti mosquito larvae. In contrast, the density of larvae in the buffer area was low to moderate. A susceptibility test showed that 0.05% cypermethrin was still susceptible to Aedes aegypti mosquitoes. Conclusion: These findings underscore the efficacy of the current control measures implemented in the study area and emphasize the critical need for continuous monitoring and surveillance. Maintaining such efforts is paramount for sustaining effective mosquito control initiatives and mitigating the potential risks posed by Aedes aegypti mosquitoes, thereby reducing the threat of vector-borne disease.